2006
DOI: 10.1007/s11154-006-9005-1
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and osteoporosis

Abstract: Anorexia nervosa (AN), a condition of severe undernutrition, is associated with low bone mineral density (BMD) in adults and adolescents. Whereas adult women with AN have an uncoupling of bone turnover markers with increased bone resorption and decreased bone formation markers, adolescents with AN have decreased bone turnover overall. Possible contributors to low BMD in AN include hypoestrogenism and hypoandrogenism, undernutrition with decreased lean body mass, and hypercortisolemia. IGF-I, a known bone troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 122 publications
1
84
0
5
Order By: Relevance
“…High levels of TGF-β1 upregulated the expression of osteoprotegerin (OPG) and downregulated the expression of RANKL by osteoblasts [2,3,7,11]. Osteopaenia, or low bone mass, and osteoporosis are among the most severe and common complications of anorexia nervosa (AN) [12][13][14][15][16]. Several studies have reported a positive relationship between body mass, body mass index (BMI), and/or bone mineral density (BMD) in adolescents with AN [15,[17][18][19][20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of TGF-β1 upregulated the expression of osteoprotegerin (OPG) and downregulated the expression of RANKL by osteoblasts [2,3,7,11]. Osteopaenia, or low bone mass, and osteoporosis are among the most severe and common complications of anorexia nervosa (AN) [12][13][14][15][16]. Several studies have reported a positive relationship between body mass, body mass index (BMI), and/or bone mineral density (BMD) in adolescents with AN [15,[17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Osteopaenia, or low bone mass, and osteoporosis are among the most severe and common complications of anorexia nervosa (AN) [12][13][14][15][16]. Several studies have reported a positive relationship between body mass, body mass index (BMI), and/or bone mineral density (BMD) in adolescents with AN [15,[17][18][19][20][21][22]. Adolescents with AN also have lower levels of biochemical markers of bone formation and resorption than normal-weight controls, indicating a decrease in bone turnover [15,[23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…Girls with AN exhibit considerable suppression of bone metabolism markers, i.e. bone-specific alkaline phosphatase, OC, C-terminal cross-linked telopeptide of type I collagen a chain (CTx), N-terminal cross-linked telopeptide of type-I collagen type I collagen a chain (NTx) and/or deoxypyridinoline [9, 10, 21-23, 60, 61] correlating with a decrease in BMD and LP levels [9,10,23]. Several authors have determined OPG concentrations in girls with AN and found that, similar to young females with AN, the girls had elevated serum levels of this cytokine [4,8,21,22,61].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Disturbances in the production, release and action of osteotropic agents, mainly hormones (including adipose tissue hormones, i.e. LP and maybe also ADIPO, RES, VISF and APE), might lead to bone mineral density (BMD) decrease or, alternatively, absence of the BMD increase expected in adolescence [9,10,23] resulting from excessive bone resorption and inadequate formation of new bone. The system of receptor activator of nuclear factor-kB ligand/receptor activator of nuclear factor-kB/osteoprotegerin (RANKL/RANK/OPG) might play an important role in this process [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Duas característi-cas clínicas da AN -deficiência estrogênica e perda de peso -são fatores de risco importantes para redução da massa óssea. É incerto se ocorre declínio progressivo e permanente na massa óssea dessas pacientes (13,14).…”
Section: Introductionunclassified